Pengaruh Nidzomul Ma’had dan Punishment terhadap Pembentukan Karakter Pancasila pada Santri Putri Pondok Pesantren Darul Lughah Wal Karomah 2 - Apriliana, Ervina; Ainol, Ainol; Inzah, M. (Universitas Nusantara PGRI Kediri, 2024)
Islamic boarding schools as Islamic educational institutions in Indonesia are a forum for developing the character of Santri. However, the challenge of achieving optimal character formation requires a comprehensive and planned strategy. The aim of this article is to find empirical evidence and analyze how nidzomul ma'had and punishment influence the formation of Pancasila character in students. The research method applied was a quantitative approach, which involved taking samples from the entire population of students at the Darul Lughah Wal Karomah 2 Islamic Boarding School, which consisted of 34 students. Data collection was carried out through the use of questionnaires, and data analysis was carried out using Structural Equation Modeling Partial Least Square (SEM-PLS). The results of the analysis show that the formation of the Pancasila character in the female students of Darul Lughah Wal Karomah 2 Islamic Boarding School is strongly influenced by nidzomul ma'had and punishment which is supported by an R-Square value of 0.577.